Overcoming the challenges encountered in CAR-T therapy: latest updates from the 2023 ASH annual conference - Zhang, Tingting; Zhang, Yicheng; Wei, Jia (Frontiers in Immunology, 2024)
Chimeric antigen receptor (CAR) -T cell therapy has entered the breakthrough era, characterized by a blend of therapeutic opportunities and challenges. With the integration of genome-editing technology, CAR-T cells will be empowered to become super warriors in eradicating tumor cells and attacking various tumors, including T-cell malignancies and acute myeloid leukemia. Notably, the optimization of CAR-T cells, including efficacy, safety, and manufacturing speed, coupled with other therapeutic strategies such as radiotherapy, hematopoietic stem cell transplantation, smallmolecule inhibitors, and bispecific antibodies, could revolutionize the therapeutic landscape of tumors. Consequently, next-generation cellular immunotherapy, including universal CAR-NK cells and synergistic combination approaches, are anticipated to significantly impact cancer treatment in the coming decade. Nevertheless, the failure rates of CAR-T therapy continue to be significant. The challenge lies in determining the optimal combination strategy and identifying reliable and robust biomarkers to effectively select the patients who will derive the greatest benefit from CAR-T therapy.Herein, we highlight recent innovations in CAR-T products, combination strategies and predictive biomarkers of response presented at the 2023 ASH Annual Meeting.